Fabrication and characterization of a three-dimensional feed-horn infrared antenna for an infrared detector - Kim, K; Han, YH; Moon, S; Park, JH; Shin, HJ (OPTICAL SOC AMER, 2004)
A three-dimensional feed-horn antenna for the 10-mum-wavelength infrared region has been suggested, characterized, and fabricated. It is applied to an infrared detector for efficient collection of infrared radiation and to reduce background noise. The optimum. size of the horn antenna was designed for maximum antenna directivity. The three-dimensional feed-horn antenna mold was fabricated by rotating and tilting illumination, whereas the antenna plate was acquired through electroplating. Antenna characteristics were measured by coupling of the antenna with a microbolometer. Measurement results show that the directivity of the antenna is 16.1 dB and the background noise is reduced by a factor of similar to2 compared with an open-structure infrared detector. (C) 2004 Optical Society of America.
Keywords: MICROBOLOMETER; RADIATION; ARRAYS